Implementation of the LADM-Based Cadastral Model for Mongolia towards Transition to a 3D Cadastre - Munkhbaatar Buuveibaatar; Kangjae Lee; Wonhee Lee (Land, 2022)
Most countries have considered the adoption of the international standard ISO 19152—Land Administration Domain Model (LADM) mostly for the improvement of their cadastral systems in the context of developing the 3D cadastre. However, the adoption of LADM is yet to be considered in Mongolia. The aim of the study is to create an LADM-based cadastral data model–Country profile for Mongolia, presenting how the standard can be tailored to the cadastral systems based on an understanding of current legal and systematic requirements. We conducted this study by taking steps to understand the current cadastral system in Mongolia, the implementation of the LADM Country profile, and the LADM conformance test for the developed model. The LADM Country profile has been created based on two parts–Administrative and Spatial. The developed country profile conformed to all classes from the low and medium levels and several classes from the high level of the Abstract Test Suite provided by the standard. In addition, we provide object-instance diagrams to help understand how the developed model can be applied to real situations. The study results will be used when considering the adoption of the standard and moving towards fulfilling modern cadastral requirements (e.g., multi-dimensional cadastres) in Mongolia.